If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4y + -4) + -1y = 11 Reorder the terms: 3(-4 + 4y) + -1y = 11 (-4 * 3 + 4y * 3) + -1y = 11 (-12 + 12y) + -1y = 11 Combine like terms: 12y + -1y = 11y -12 + 11y = 11 Solving -12 + 11y = 11 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 11y = 11 + 12 Combine like terms: -12 + 12 = 0 0 + 11y = 11 + 12 11y = 11 + 12 Combine like terms: 11 + 12 = 23 11y = 23 Divide each side by '11'. y = 2.090909091 Simplifying y = 2.090909091
| 6x-12x-5=0 | | 1/9x-5/3=0 | | 12(1/4)-8(3/10) | | 12x-4=3(x+1)-x | | 6x-4y=-20 | | 7÷2(1/5) | | -8*7-7y=56 | | 7x^2+5x-14=34-29x | | cosx=7x | | y=6x^2+6 | | X-8+1=3x | | -8*8-7y=56 | | 2+5x=6*(x-4) | | -8-8-7y=56 | | -8-8-7=56 | | x+y+z=2004 | | 50x+30y=600 | | X(2x-5)(4x+3)=0 | | Z=20x+60y | | -20/-0.02 | | 1/10-(-5/3) | | 3x^2y^2+24xy+1=0 | | 0=.5mv^2 | | x^2+13xy+36y^2= | | m^3+6m^2+9m=0 | | 6c-9=3c-18 | | -37t+5t^2-24=0 | | 5y^2+3x^2+19=4x-2x^2-20y | | 1+3x^2+x^4=0 | | 2-7a-6a=2 | | 19-a+4a=4 | | 3y+y=-36 |